PERSONAL SELF-DEVELOPMENT IN THE FRAMEWORK OF STUDENT-CENTERED STRATEGY OF MODERN TEACHING INNOVATIONS - Elena Valeryevna Murugova (Advanced Engineering Research)
The article is intended to cover the new strategies to individual activity of students dealing with the self-management of study process organization providing quality higher education, strengthening mobility for better learning in the framework of competence/learning outcome-based, student-centered approaches to learning, teaching and assessment. It presents the main competences of individual activity throughout students’ careers, major tasks and trends of individual activity, essential criteria for individual work assessment and modern teaching technologies.